Peran Artificial Intelligence dalam Pembelajaran Bahasa Arab: Peluang dan Tantangan - Fahmi, Muhamad; Syifaul Adhimah (Journal of Practice Learning and Educational Development, 2024)
The study explores the role of Artificial Intelligence (AI) in Arabic language learning, with an emphasis on the opportunities and challenges faced in its application. AI has great potential to revolutionize the way languages are learned by offering personalized materials to suit the individual needs of students, adapting teaching methods based on different learning styles, and providing real-time feedback to accelerate the learning process. Through in-depth data analysis, AI can tailor teaching to be more relevant and effective, thereby enhancing student engagement and learning outcomes. Despite offering many advantages, the application of AI faces several significant challenges, such as the availability of adequate quality data, the quality of algorithms that need to be well designed to produce accurate results, and the resistance to new technologies from educators as well as students. The study uses a library study method to study the latest literature on the application of AI in Arabic language education, identifying the benefits and obstacles. Research findings show that while AI can enhance learning processes, contextual adjustment and in-depth understanding of the application of this technology is crucial to maximizing its benefits in education.